News reaction in financial markets within a behavioral finance model with heterogeneous agents - Thomas Fischer (Technische Universität Darmstadt, Department of Law and Economics, 2011)
This paper presents a Heterogeneous Agent Model of a financial market with chartist and fundamentalist traders that exhibit bounded rationality and short-term thinking to explain the effect of under and overreaction to news. The existence of the Market Maker's finite price adjustment speed leads to the fact that prices do not adjust instantaneously to new information. Chartists use moving average rules to make their investment decisions. Chartist can transform an underreaction-only scenario into a market with overreaction. The use of long moving average rules might even make the market unstable. Furthermore, noise in financial markets can lead to long time decoupling from fundamental value. Higher market efficiency (low deviations from fundamental value), on the other hand, is achieved if high rationality and long-term thinking for the agents is assumed.
Keywords: G14; D84; C62; C15; 330; Heterogeneous; Agent; Model; stock market; under and overreaction to news; moving average rules; financial stability; Wirtschaftsinformation; Ankündigungseffekt; Börsenkurs; Wertpapierhandel; Anlageverhalten; Finanzanalyse; Agentenbasierte Modellierung; Gleichgewicht; Theorie